"I Tried Forcing Myself to do It, but Then It Becomes a Boring Chore": Understanding (dis)engagement in Physical Activity Among Individuals With Type 2 Diabetes Using a Practice Theory Approach. (February 2022) - Thorsen, Ida K.; Kayser, Lars; Teglgaard Lyk–Jensen, Helle; Rossen, Sine; Ried-Larsen, Mathias; Midtgaard, Julie
Lack of physical activity (PA) is common among individuals with type 2 diabetes (T2D). We apply a practice theory approach to investigate PA engagement in the context of T2D. Data were collected through semi-structured individual interviews ( n = 23) and focus groups ( n = 3x6) and analyzed by deductive-inductive reflexive thematic analysis using a practice theory framework. Forty-one purposefully selected individuals with T2D (29 men) between the ages of 54 and 77 years were included. The analysis resulted in three main themes informed by five subthemes, reflecting the key elements of practice theory (i.e., meanings, materialities, and competencies). One overarching theme identified PA engagement as an unsustainable and insurmountable project in constant and unequal competition with the practice of physical inactivity. To increase PA among individuals with T2D, future PA interventions and strategies should aim to establish a stronger link between PA and everyday life practices.